Interactions of daylength, temperature and nutrients affect thresholds for life stage transitions in the kelp Laminaria digitata (Phaeophyceae) - Martins, Neusa (2017)
Kelp beds worldwide are under pressure from ongoing climate and environmental change. Along European coastlines increases in seawater temperature and changes in nutrient conditions occur where upwelling events are disrupted and also along eutrophicated coasts. In addition, seaweed responses to change may interact with seasonal daylength cycles. We performed a factorial experiment to examine the combined effects of seawater temperatures, nutrient regimes and photoperiod (long and short days) in order to better understand how latitudinal or seasonal differences in daylengths affect the sensitivity of transient microscopic kelp stages of Laminaria digitata from the North Sea to warming and eutrophication. While the optimal temperature range for vegetative gametophyte growth was 10 degrees C-18 degrees C under long summer photoperiod conditions, gametogenesis was induced at lower temperatures between 5 degrees C and 15 degrees C, with maximum sporophyte development under long photoperiods and enriched nutrient regimes, which represent local late spring conditions. Although gametogenesis was fastest at 10 degrees C-15 degrees C, sporophyte recruitment was highest at 5 degrees C. As these particular early life cycle processes in L. digitata have different temperature optima, this may drive the seasonal cycle of recruitment in the field. Increasing summer temperatures due to global warming will increase gametophyte size due to enhanced vegetative growth and inhibition of gametogenesis. This will probably lead to delayed but enhanced recruitment of new sporophytes under cooler autumn to spring conditions over a wide geographical scale, preventing the formation of juvenile sporophytes under stressful summer conditions and possibly changing annual recruitment patterns.